A Class of Variable Elasticity of Substitution Production Functions - Revankar, Nagesh S. (Econometrica, 1971)
[We introduce and analyze a class of variable elasticity of substitution (VES) production functions for which the substitution parameter varies linearly with the capital-labor ratio around the intercept term of unity. The VES function contains as special cases the more important special cases of the well known CES function. In terms of some familiar economic relationships, the VES posits a linear view of the world in contrast to the log-linear view posited by the CES function.]